An improved light efficiency LED array design via increasing uniformity for pea sprouts - Du, Li; Xu, Yang; Wang, Can; Chen, Yiyi; Zhang, Junhua; Ma, Bin; Chen, Danyan (Biosystems engineering, 2025)
Light distribution is an important factor affecting plant growth under facility lighting. However, traditional lighting provides uneven illumination, which increases the difficulty of cultivation management and creates challenges in standardised plant production. Achieving the best light environment is highly significant for high-efficiency production. To effectively address uneven light distribution in the planting layer, this study proposed a high light efficiency LED array design that increases light distribution uniformity based on the improved genetic algorithm. This design has been verified by optical simulation, spectrometer measurement and pea sprout cultivation. The simulation results showed that the illumination uniformity of the optimised LED array and traditional square LED array were 91.7 % and 85.7 %, respectively. The uniformity of the illuminance measured by the spectrometer for two LED arrays was 92.5 % and 80.2 %, respectively. Furthermore, the effects of the two LED arrays on the growth of pea sprouts were compared. The total light intensity of the optimised LED array was reduced by 20.1 % lower; however, the yield of the pea sprouts increased by 8.6 % higher. The light intensity required to produce pea sprouts per unit mass was 26.5 % lower, while the energy and economic efficiency improved. Therefore, the LED array designed based on the improved genetic algorithm has high illumination uniformity and light use efficiency and presents a novel method for improving pea sprout production and lighting optimisation strategy. •Proposed an LED layout optimisation method based on improved genetic algorithm.•The optimised LED array improves energy efficiency and light use efficiency.•Obtained more and stronger pea sprouts by uniform light.